2004
DOI: 10.1002/glia.10359
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of constitutive nitric oxide synthases regulated by voltage‐gated Na+ and Ca2+ channels in cultured human astrocytes

Abstract: We report the functional characterization of constitutive nitric oxide synthase(s) (NOS) such as neuronal and endothelial NOS in cultured human astrocytes. Exposure of cultured human astrocytes to 1 microM veratridine or 50 mM KCl produced a pronounced increase in a calmodulin-dependent NOS activity estimated from cGMP formation. The functional expression of voltage-gated Na(+) channel, which is estimated by the response to veratridine, appeared to be earlier (at second day in culture) than that of voltage-gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 61 publications
1
10
0
1
Order By: Relevance
“…Different sources of NO have been demonstrated in the nervous system. Neurons, astrocytes, and endothelial cells have been shown to express constitutive NOS (neuronal and endothelial NOS isoforms) (6,34,36,40,49,50). Activation of the group I mGluRs in astrocytes increases intracellular Ca 2ϩ , which, in turn, results in the release of Ca 2ϩ -dependent vasoactive substances such as prostaglandins and NO (56).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different sources of NO have been demonstrated in the nervous system. Neurons, astrocytes, and endothelial cells have been shown to express constitutive NOS (neuronal and endothelial NOS isoforms) (6,34,36,40,49,50). Activation of the group I mGluRs in astrocytes increases intracellular Ca 2ϩ , which, in turn, results in the release of Ca 2ϩ -dependent vasoactive substances such as prostaglandins and NO (56).…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, NO is a potent signal released by neurons, astrocytes, and endothelial cells (6,34,36,40). A recent study from our laboratory showed that NFATc3 nuclear accumulation in extracerebral VSMCs depends on both Ca 2ϩ influx and PKG activation through endothelium-derived NO (17).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(102) On the other hand, there is emerging evidence that VGSC activity may control NO production. (103) In strongly metastatic Mat-LyLu rat prostate cancer cell line, inhibition of VGSC activity with the highly specific blocker tetrodotoxin increased NO release. (104) For the way forward, in order to achieve better and more consistent understanding of the effects of NO in metastasis, the following would be essential.…”
Section: General Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Τα αποτελέσματα των πειραμάτων αυτών δείχνουν ότι σε χαμηλή συγκέντρωση ασβεστίου (Σχήμα 10) ή σε παρουσία βεραπαμίλης (Σχήμα 11) στο διάλυμα, η παρουσία του L-NAME δεν μεταβάλλει την ανταποκρισιμότητα των ΛΜΙ στην ACh υποδηλώνοντας ότι σε τάση ηρεμίας 2.5 γραμμαρίων η παραγωγή του NO προάγεται από την είσοδο ασβεστίου από τον εξωκυττάριο χώρο κυρίως μέσω τασεοεξαρτώμενων διαύλων ασβεστίου. Κατά συνέπεια, η παραγωγή του NO, απαιτεί φυσιολογική εξωκυττάρια συγκέντρωση ασβεστίου και εξαρτάται από την είσοδο στο κύτταρο ιόντων ασβεστίου μέσω διαύλων ιόντων εξαρτώμενων από την τάση τύπου L [163] και άρα οι αποκλειστές διαύλων ιόντων ασβεστίου τύπου L [164,165] μπορούν να επηρεάσουν την έκφραση και/ή την δραστηριότητα της NOS. Τα αποτελέσματά μας δείχνουν ότι η επίδραση της τάσης ηρεμίας στην ανταποκρισιμότητα των ΛΜΙ στην ACh είναι ασβεστιοεξαρτώμενη.…”
Section: τα δεδομένα προέρχονται από τον μέσο όρο των τιμών 5 πειραμάunclassified